Site fertility and soil water‐table level affect fungal biomass production and community composition in boreal peatland forests. (9th January 2021) - Peltoniemi, Krista; Adamczyk, Sylwia; Fritze, Hannu; Minkkinen, Kari; Pennanen, Taina; Penttilä, Timo; Sarjala, Tytti; Laiho, Raija
Summary: A substantial amount of below‐ground carbon (C) is suggested to be associated with fungi, which may significantly affect the soil C balance in forested ecosystems. Ergosterol from in‐growth mesh bags and litterbags was used to estimate fungal biomass production and community composition in drained peatland forests with differing fertility. Extramatrical mycelia (EMM) biomass production was generally higher in the nutrient‐poor site, increased with deeper water table level and decreased along the length of the recovery time. EMM biomass production was of the same magnitude as in mineral‐soil forests. Saprotrophic fungal biomass production was higher in the nutrient‐rich site. Both ectomycorrhizal (ECM) and saprotrophic fungal community composition changed according to site fertility and water table level. ECM fungal community composition with different exploration types may explain the differences in fungal biomass production between peatland forests. Melanin‐rich Hyaloscypha may indicate decreased turnover of biomass in nutrient‐rich young peatland forest. Genera Lactarius and Laccaria may be important in nutrient rich and Piloderma in the nutrient‐poor conditions, respectively. Furthermore, Paxillus involutus and Cortinarius sp. may be important generalists in all sites and responsible for EMM biomass production during the first summer months. Saprotrophs showed a functionally more diverse fungal community in the nutrient‐rich site.